Development of silica-supported frustrated Lewis pairs: highly active transition metal-free catalysts for the Z-selective reduction of alkynes. Issue 3 (22nd October 2015) - Szeto, Kai C.; Sahyoun, Wissam; Merle, Nicolas; Castelbou, Jessica Llop; Popoff, Nicolas; Lefebvre, Frédéric; Raynaud, Jean; Godard, Cyril; Claver, Carmen; Delevoye, Laurent; Gauvin, Régis M.; Taoufik, Mostafa
Abstract : Supported Lewis acid/base systems based have been prepared and characterized. Abstract : Supported Lewis acid/base systems based on a triphenyl phosphine fragment and Piers' reagent (HB(C6 F5 )2 ) or BArF have been prepared and characterized. Both materials show unprecedented catalytic activity in the Z -selective hydrogenation of 3-hexyne to Z -3-hexene with a selectivity up to 87%. Other alkynes can also be hydrogenated Z -selectively, albeit with moderate yields. The activity of the supported phosphine/HB(C6 F5 )2 adduct is similar to the only homogeneous example reported thus far based on bridged B/N frustrated Lewis pairs under high hydrogen pressure. Importantly, this transition metal-free supported catalyst was recycled five times in the challenging selective hydrogenation of a non-polar unactivated alkyne.